PENINGKATAN KEMAMPUAN TEKNIK VOKAL PESERTA DIDIK KELAS VIII B DI SMP NEGERI 1 MEMPAWAH HILIR - Prasetyo, Fernando Willy; Ghozali, Imam; Sagala, Mastri Dihita (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2024)
The purpose of this study is to improve the seventh-grade (VII B) pupils at SMP Negeri 1 Mempawah Hilir's vocal technique competency. To provide students a better understanding of singing technique, an innovative method is needed in the context of cultural arts education. To get the best outcomes, the drill method was selected as the teaching approach. The purpose of the study is to determine how well students' voice technique can be improved through the drill approach and how this can affect their learning outcomes in cultural arts education.This action study is divided into two cycles, with the drill approach being implemented in the second cycle following reflection on the first cycle's flaws. The students' vocal technique abilities were assessed by group assessments, individual testing, and observation.The study's findings show that students' voice technique skills significantly improved in the second cycle. 92.59% of students met the good criteria, according to the evaluation, and 7.41% met the excellent criteria. Students in the second cycle performed better than in the first, with an average score of 79.47. The application of the drill approach is helpful in improving the vocal technique skills of seventhgrade students at SMP Negeri 1 Mempawah Hilir, according to the research findings. This demonstrates that, when used to cultural arts education, the drill approach can be a useful teaching tactic that enhances student learning outcomes.